Pola Pertumbuhan Dan Reproduksi Ikan Lumo (Labiobarbus ocellatus) di Sungai Tulang Bawang Provinsi Lampung - Alwan Tholifin; Berta Putri; Rara Diantari; Indra Gumay Yudha (Jurusan Perikanan dan Kelautan, 2014)
Lumo (Labiobarbus ocellatus) is one of consumption fish that available throughout the year at Tulang Bawang river.The constrains to local fish populations is reducing fish stocks by fisherman. Information about growth and reproduction of lumo is necessary to support the management of fish resources. The research was conducted on April until December 2013. The samples were collected from 4 stations and from the fisherman who landed at fish market The parameters that were measured included of the length and weight, the gonade somatic level, the gonade somatic index and fecundity. Fish samples were used for this study is 893 fish. The result showed that lumo spawned from November to Desember and categorized as total spawner. The gonade maturity index varied from 2.22 to 7.27%, fecundity ranged from 424 to 24.491 eggs, the sex ratio of lumo is unbalanced.The growth pattern were positive allomatric and condition factor is <1 in which showed lumo in Tulang Bawang river is flat